The Role of Financing Management and Infrastructure in Improving The Quality of Education In Elementary Schools - Risdiyani, Heri; Jumintono, Jumintono; Saryanto, Saryanto (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to determine the role of financing management and infrastructure facilities in improving the quality of education at SD Negeri 1 Bumirejo, Mojotengah District, Wonosobo Regency. This type of research is a type of qualitative research with a case study approach. Primary data was obtained directly through observation at SD Negeri 1 Bumirejo, Mojotengah District and interviews with Principals, Teachers, Committees, and students. The source of data comes from school financial documents, inventory lists of facilities and infrastructure, and academic data such as student learning outcomes and school activity reports. Data collection techniques are observation, interviews, and documentation. The data analysis in this study is a qualitative analysis. The results of this study conclude that financing management at SD Negeri 1 Bumirejo is carried out with the principles of transparency, participation, and accountability. The School Operational Assistance Fund (BOS) is the main source that is optimally utilized to support learning activities, procurement of learning facilities, and improve teacher competence. The involvement of school committees and teachers in the preparation of RKAS strengthens the quality of planning and the effectiveness of the use of budgets and facilities and infrastructure in schools plays an important role in improving the quality of learning. Facilities such as decent classrooms, libraries, projectors, and props contribute to increased student interest and understanding. Although not entirely ideal, the use of available facilities has had a positive impact on the educational process.